Improvement of Maneuverability and Stability for Eight wheel Independently Driven Electric Vehicles by Direct Yaw Moment Control - Cai, Lichun; Liao, Zili; Wei, Shuguang; Li, Jiaqi (International Conference on Electrical Machines and Systems (Online), 2021)
This paper proposes a direct yaw moment controller for improving the steering maneuverability and stability of eight wheel independently driven (8WID) electric vehicles. Firstly, a dynamic vehicle model is developed based on the two degree of freedom model. After that, the control strategy is divided into upper and lower layer, of which a tracking controller and an anti-slip controller is designed, respectively. The upper controller applies fuzzy PID to track the yaw rate. The lower controller utilizes two sliding mode controllers to realize the anti-slip control, which are designed by considering the backstepping method. Finally, the proposed control strategy is validated through hardware-in-loop real-time simulation.